IMPLEMENTATION OF POLITICAL COMMUNICATION FOR LEGISLATIVE CANDIDATES VIA INSTAGRAM SOCIAL MEDIA IN THE 2024 DPR RI LEGISLATIVE ELECTION (Case Study of Legislative Candidate I Nyoman Parta, S.H Bali Electoral District) - Alit Pratiwi, Ketut; I Gusti Agung Laksmi Swaryputry; Ni Kadek Hera Yuni Arina (Bajang Institute, 2025)
Along with the development of digital technology, the political arena of the 2024 Legislative Election has become increasingly dynamic, especially on Instagram social media. Instagram is used by legislative candidates (caleg) to build more interactive political communication with their followers on social media. This study focuses on the implementation of political communication through Instagram carried out by I Nyoman Parta, S.H., a legislative candidate for the Indonesian House of Representatives for the Bali Electoral District. The aim is to analyze the implementation of communication carried out by I Nyoman Parta in implementing his political campaign on Instagram. The research method used is a qualitative case study with a descriptive approach. Data were collected through observations on Instagram activities, including upload patterns, interactions with voters, and types of content shared. Interviews and documentation were also conducted in data collection to strengthen the research results. The results of the study show that Instagram is actively used by I Nyoman Parta in conveying political messages, interacting with voters, and building a positive political image assisted by the admin and social media team from Mr. Nyoman Parta's Instagram. The implementations applied include the use of attractive visuals, as well as the use of Instagram features.